Metodyczne aspekty szacowania wartości przedsiębiorstwa - Franc-Dąbrowska, Justyna (The article presents problems of the procedure of preparing and meaning cash budget in management process. The author defined and described particular elements of cash budgeting process in enterprises. There are discussed effects of a cash budget in management process in enterprises., 2006)
This paper presents models of corporate valuation including Modigliany's and Miller's evolution theory and also statistical methods used in business practices. Special attention was paid to importance of subjective approach in practical methods of enterprise value estimation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 84-94